The learning and transformative potential of the social library in prison - Marta Pampaloni (Firenze University Press, 2024)
This article presents the outcomes of a doctoral research focused on the prison library service, which is recognized as essential within prison context to support the growth of the prisoners in a holistic sense. Within the theoretical-scientific framework of experiential learning, transformative learning, adult learning in prison and prison library, the library service was re-interpreted and organized, starting from the social library model, as a learning device capable of promoting self-directed-learning processes from a personal and organizational transformative perspective.   Il potenziale formativo e trasformativo della biblioteca sociale in carcere. Il contribuito presenta gli esiti di una ricerca dottorale in cui l'attenzione si è focalizzata sul servizio bibliotecario penitenziario, riconosciuto come essenziale all'interno dei contesti penitenziari per supportare la crescita in senso olistico dei ristretti. All'interno del framework teorico-scientifico dell'experiential learning, del transformative learning, dell'adult learning in prison e della prison library, il servizio bibliotecario è stato re-interpretato e organizzato, a partire dal modello di biblioteca sociale, come un dispositivo formativo in grado di promuovere processi di auto-apprendimento in ottica trasformativa sia personale che dell'intera organizzazione penitenziaria.